The Effect of Village Officers’ Role, Village Officers’ Performance, and Monitoring System on the Accountability of Village Fund Management - Hisanah Humaira; Jalaluddin Jalaluddin; Gamal Batara (Universitas Syiah Kuala, 2022)
This study aims (1) to examine the effect of village officers’ role on the accountability of village fund management, (2) to examine the effect of village officers’ performance on the accountability of village fund management, (3) to examine the effect of monitoring system on the accountability of village fund management, and (4) to examine the influence of village officers’ role, village officers’ performance, and monitoring system on the accountability of village fund management simultaneously. The population in this study consist of villages in Banda Aceh City, with total of 47 villages. The respondents are the village head, village secretary, and village finance officer who take parts in managing village funds, thus the total respondents are 141 respondents. Data are collected using questionnaires that was distributed directly to respondents from March to June 2021. The analytical method used is multiple linear regression with the SPSS v.25. The results show that the village officers’ rp;e, vilalge officers’ performance, and the monitoring system have a significant effect on the accountability of village fund management.